Pengalaman Sekolah Penyelenggara Pendidikan Inklusif dalam Menyediakan Pembelajaran Sains - Suprihatiningrum, Jamil (INKLUSI, 2022)
This article focuses on the investigations towards challenges and obstacles faced by Schools Providing Inclusive Education (SPIE) in creating inclusive science learning for students with disabilities. Under the qualitative research lense, three SPIE (Sekolah Mutiara, Permata and Berlian) in the Special Province of Yogyakarta were involved and thirteen respondents (principals, science teachers, support teachers) were selected through purposive sampling technique. Data were collected by in-depth interviews and followed by a Focus Group Discussion (FGD) with six science teachers. Collected data were then analyzed through coding, categorization, and four themes were generated. The findings show that types of disabilities possessed by students are very diverse, so that teachers need more effort and time to manage class. Support for the teachers and science learning media were limited. Another finding shows that contradictions between policies on inclusive education resulted in the confusion of implementing inclusive education in school level. Artikel ini membahas tantangan dan hambatan yang ditemui oleh Sekolah Penyelenggara Pendidikan Inklusif (SPPI) dalam menyediakan pembelajaran sains untuk siswa difabel. Tiga SPPI di Daerah Istimewa Yogyakarta dicakup dalam penelitian ini, dengan tiga belas responden yang terdiri atas kepala sekolah, guru sains, guru pendamping kelas (GPK). Data dikumpulkan dengan wawancara mendalam dan Focus Group Discussion (FGD) bersama enam guru sains. Hasil analisis data menunjukkan di ketiga SPPI, variasi tipe dan jenis disabilitas yang dimiliki oleh siswa sangat beragam, sehingga guru membutuhkan tenaga dan waktu lebih banyak untuk mengelola pembelajaran. Daya dukung sekolah masih kurang dan perlu ditingkatkan terutama di area jumlah GPK dan media pembelajaran yang sesuai untuk siswa dengan jenis disabilitas tertentu. Sekolah Berlian menunjukkan iklim pembelajaran yang lebih inklusif dibanding yang lain. Ditemukan adanya kontradiksi antar-kebijakan pemerintah mengenai pendidikan inklusif, yang mengakibatkan pelaksana pendidikan inklusif di sekolah mengalami kebingungan.